Structural monitoring in road works using the RTK / NTRIP technique: Data analysis, development and implementation of a positional alert system (Research, Society and Development, 2021)
Since the expansion of the highway system in Brazil in the 1930s, there has been a scenario with numerous road works in different conditions of use and safety. This fact is worrying due to the lack of adequate monitoring in OAEs (Special Works of Art) and by whom in fact these structures must be monitored. These structures are subject to the actions of static and dynamic forces, which can cause displacements and / or deformations that are characterized by their amplitude, direction and temporal behavior. There are also deterioration processes, whether due to wear and tear or natural stresses, leading to the weakening of the structure. The incorporation of inspection and monitoring methods in the structural behavior in OAEs is increasing due to the high cost of recovery of these works. However, it is necessary to have a continuous or periodic monitoring plan, according to the permissible quantities of each structure. The technology of GNSS (Global Navigation Satellite Systems) through the methodology of survey RTK (Real Time Kinematic), was able to offer support in real time in the control of structural deformations. In this context, SiGE (Structural Management System) was developed for monitoring and issuing alerts about events previously determined by the system operator. By obtaining this data in real time, it is possible to evaluate the safety of the structure in service, monitor the structure continuously and safely and improve future projects with the definition of maximum structural displacements.